Report of the Steering Committee on Youth Affairs and Sports for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, Government of India, 2001)
The Steering Committee Report on Youth Affairs and Sports for the Tenth Five Year Plan presents a comprehensive strategy to harness India’s vast youth population—estimated at nearly 700 million under the age of 35—as a driving force for national development. Building upon the achievements of the Ninth Five Year Plan, the report evaluates progress in youth engagement, education, employment generation, and community service while outlining an expanded and integrated framework for the period 2002–2007. It highlights the significant growth of institutions such as Nehru Yuva Kendra Sangathan and the National Service Scheme in mobilizing rural and urban youth toward nation-building activities. Emphasizing youth empowerment, gender justice, leadership development, inclusivity, and improved access to health and education, the report advocates a cohesive policy structure linking youth affairs with sports development. A major thrust is placed on strengthening sports infrastructure, promoting grassroots participation, integrating sports into educational curricula, and expanding partnerships with NGOs for effective program delivery. With a proposed financial allocation of ₹3287.51 crores—representing a fourfold increase over the previous plan—the strategy underscores the government’s commitment to expanding opportunities, enhancing institutional capacity, and positioning youth as central contributors to India’s socio-economic progress.
Government of India Planning Commission October - 2001
Keywords: Youth Empowerment; Sports Development; Tenth Five Year Plan; National Development; Nehru Yuva Kendras; National Service Scheme; Gender Justice; Rural Youth Outreach; Sports Infrastructure; Youth Policy Framework; Community Participation; Financial Allocation